Development of a cost effective technique to eliminate conventional finishing operation applying high speed end milling of silicon - Amin, A. K. M. Nurul; Patwari, Muhammed Anayet Ullah; M., Dali; M.I., Musa (2010)
Silicon has been widely used in different branches of industrial engineering. Most application of silicon is in computer parts or hardware especially for the production of integrated circuit (IC) chips. Machining of silicon is a big challenge and expensive affair because of it inherent brittleness which is a major limitation as the process of removing the material can generate subsurface damage. Silicon is conventionally finished using grinding followed by polishing and lapping to achieve required surface finish and surface integrity...